Business Process Management Capabilities in Local Governments: A Multi-Method Study - Niehaves, Björn; Plattfaut, Ralf; Becker, Jörg (Government Information Quarterly, 2013)
Business Process Management (BPM) is a topic of greatest relevance to government innovation. While the concept originally stems from the private sector, public sector organizations have established BPM capabilities and are in the move of developing these further. Despite the importance of the phenomenon, literature does however not yet provide a comprehensive picture of BPM capabilities in governments. In this paper, we thus examine BPM capabilities on the local government level by means of an intertwined quantitative survey and (representative) qualitative in-depth case study. We identify a set of BPM challenges and reflect on the power of prevalent BPM capability assessment and development models, mostly maturity models, to provide good guidance. We suggest taking into account organizational positions in order to overcome the significant shortcoming of the ‘maturity’ concept, especially the focus on convergence towards an “ideal” state. Thus, we argue for developmental models following divergence theories. Implications for practice and potentially fruitful avenues for future research are discussed in the light of our findings.